A values-laden history: Jeffrey Klaiber S. J. and the historiography of the Jesuits in Latin America - Fulkerson S. J., Taylor (2020)
As a historian of the Jesuits in Latin America, Jeffrey Klaiber S. J. has contributed not only to the study of missions and the restoration of the Jesuits in Latin America, but also has developed a historical vision distinct from other historiographical currents. His emphasis on certain values —modernity, inculturation and continuity if the way of proceeding of the Society of Jesus— has roots in his own Jesuit identity. Linking this vision with the development of Jesuit studies according to John O’Malley S. J., this essay seeks to interpret what distinguishes Klaiber’s contribution.